Comparison of antibiotic resistance pattern among Enteropathogenic bacteria isolated from broiler and backyard chicken meat - Yulistiani, R.; Praseptiangga, D.; Supyani, S.; Sudibya, S. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
This study aimed to compare the antibiotic resistance patterns among original Enterobacteriaceae isolates from broiler and backyard chicken meats in Surabaya, Indonesia, isolated in 2016-2017. The Kirby–Bauer disk diffusion method was used to determine the resistance of these isolates against tetracycline (TE), gentamicin (CN), cefoxitin (FOX), sulfamethoxazole-trimethoprim (SXT), nalidixic acid (NA), and chloramphenicol (C). Both broiler and backyard chicken meat isolates were resistant to the six antibiotics tested. Overall, broiler meat isolates which resistant to TE, CN, FOX, SXT, NA, C were 57.76% higher than backyard chicken meat isolates. More than 50% of broiler meat isolates (304 samples) were resistant to TE and NA, whereas backyard chicken meat isolates (310 samples) were only resistant to TE. The resistant strains found in both meat isolates were Salmonella spp., Escherichiacoli, Shigella spp., Citrobacter spp., Klebsiella spp., Yersinia spp., Proteus spp., Enterobacter spp., Serratia spp., and Edwardsiella spp. Resistant strains of broiler meat isolates were significantly higher (P<0.05) than backyard chicken meat isolates, except Edwardsiella spp. Overall, multidrug-resistant Enterobacteriaceae was found to be higher in broiler meat isolates than in backyard chicken meat isolates. Broiler and backyard chicken meats are potential reservoirs of multidrug-resistant Enterobacteriaceae which threat to public health.